Exploring the Impact of GitHub Copilot on Health Informatics Education - Avramovic, Sanja; Avramovic, Ivan; Wojtusiak, Janusz (Applied Clinical Informatics, 2024)
Background The use of artificial intelligence-driven code completion tools, particularly the integration of GitHub Copilot with Visual Studio, has potential implications for Health Informatics education, particularly for students learning SQL and Python.Objectives This study aims to evaluate the effectiveness of these tools in solving or assisting with the solution of problems found in Health Informatics coursework, ranging from simple to complex.Methods The study assesses the performance of GitHub Copilot in generating code to solve programming problems normally given to students in introductory Health Informatics programming courses. Problem statements are provided to the tool; the response is assessed on correctness. The focus is on the impact of detailed explanations on the tool's effectiveness.Results Findings reveal that GitHub Copilot can generate correct code for straightforward problems. The correctness and effectiveness of solutions decrease with problem complexity, and the tool struggles with the most challenging problems, although performance on complex problems improves with more detailed explanations.Conclusion The study not only underscores the relevance of these tools to programming in Health Informatics education but also highlights the need for critical evaluation by students. It concludes with a call for educators to adapt swiftly to this rapidly evolving technology.
Keywords: GitHub copilot; visual studio; health informatics education; SQL; Python